2020
DOI: 10.3389/fpls.2020.00240
|View full text |Cite
|
Sign up to set email alerts
|

Cynara cardunculus L. as a Multipurpose Crop for Plant Secondary Metabolites Production in Marginal Stressed Lands

Abstract: Cardoon (Cynara cardunculus L.) is a Mediterranean crop, member of the Asteraceae family, characterized by high production of biomass and secondary metabolites and by a good adaptation to climate change, usable in green chemistry, nutraceutical, and pharmaceutical sectors. Recent studies demonstrated the ability of cardoon to grow up in a stressful environment, which is associated with enhanced biosynthesis of biologically active compounds in these plants, and this effect is increased by abiotic stresses (salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Plant development and yield are strongly affected by mineral nutrition and environmental stresses that reallocate resources from primary to secondary metabolism with a direct effect on product quality [ 15 ]. In some species it has been shown that salt stress induced the synthesis of substances in proportion to the increase in NaCl concentrations, confirming the important role of these molecules for the tolerance to stress conditions in plants and salinity as an efficient technique for increasing the secondary metabolite content in plants [ 17 ]. However, little information on the phytochemical profile of V. locusta can be found, with the exception of some recent works [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant development and yield are strongly affected by mineral nutrition and environmental stresses that reallocate resources from primary to secondary metabolism with a direct effect on product quality [ 15 ]. In some species it has been shown that salt stress induced the synthesis of substances in proportion to the increase in NaCl concentrations, confirming the important role of these molecules for the tolerance to stress conditions in plants and salinity as an efficient technique for increasing the secondary metabolite content in plants [ 17 ]. However, little information on the phytochemical profile of V. locusta can be found, with the exception of some recent works [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…sylvestris Lamk Fiori). Commonly known as cardoon or artichoke thistle, it is widely used due to its multifaceted properties not only as a food ingredient but also in various industrial applications [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the former are phenolic compounds, whose chemical structure allows hydrogen atom transfer mechanisms (HAT) to occur via a pure H transfer, or an electron transfer followed by a proton release, or a proton loss followed by an electron transfer [ 28 ]. In Cynara , a plant mainly found in arid and semi-arid regions often subjected to salinity, NaCl stress induces the synthesis of phenolic substances in proportion to the increase in salt concentration and this increase in salinity has proven to be a good technique to enhance the secondary metabolite content in plants grown for nutraceutical use [ 29 ]. Among the most common secondary metabolites found at higher levels in plants stressed by salt are isoorientin, orientin, vitexin, rutin [ 30 ], as well as phenolic acids [ 31 ].…”
Section: Salinity Stressmentioning
confidence: 99%